Can a non-invasive strategy for managing young dyspeptics be safely implemented in Asia? - Mahadeva, Sanjiv; Goh, Khean-Lee (Blackwell Publishing, 2003)
Dyspepsia is a common problem in the Asia-Pacific region, with a prevalence rate ranging from 10-20%. It constitutes 2-5% of consultations with primary-care physicians and forms a major part of the gastroenterologists' workload. Although upper gastrointestinal endoscopy (UGIE) is the investigation of choice, no serious disease is present in the majority of patients and various other ways have been suggested, mainly in the West, to reduce the demand on the finite resources of UGIE services. The alternative methods to UGIE have been based on non-invasive detection of Helicobacter pylori in patients with dyspepsia, as the organism has been shown to be associated with most peptic ulcers and even gastric cancer. A positive H. pylori test in a patient with dyspepsia may not necessarily indicate serious disease, but H. pylori eradication eliminates the propensity for developing peptic ulcers and perhaps even cancer (not proven). In high-risk populations, non-invasive screening for H. pylori can even be considered a 'cancer test', as it can help target investigations in a selected group of patients.